1998
DOI: 10.1038/sj.bjp.0701853
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prostanoid receptor‐evoked responses in rat sensory neurones

Abstract: 1 Prostanoid receptor-mediated sensitization, or excitation, of sensory nerve ®bres contributes to the generation of hyperalgesia. To characterize the prostanoid receptors present on sensory neurones, biochemical assays were performed on primary cultures of adult rat dorsal root ganglia (DRG) and the F-11 (embryonic rat DRG6neuroblastoma hybrid) cell line. 2 In DRG cultures, the IP receptor agonists, cicaprost and carbaprostacyclin (cPGI 2 ) stimulated cyclic AMP accumulation. Prostaglandin E 2 (PGE 2 ) also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 68 publications
7
68
1
1
Order By: Relevance
“…In nodose neurons, PGD 2 inhibited postspike hyperpolarization, resulting in an increase in the firing frequency (5). Extracellular recording of direct-current potentials indicated that PGD 2 perfusion caused a depolarization response of vagal C fibers (25). However, in another study using in vivo electrophysiological single-unit recording from rat trigeminal ganglion, PGD 2 failed to sensitize meningeal nociceptors (34).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In nodose neurons, PGD 2 inhibited postspike hyperpolarization, resulting in an increase in the firing frequency (5). Extracellular recording of direct-current potentials indicated that PGD 2 perfusion caused a depolarization response of vagal C fibers (25). However, in another study using in vivo electrophysiological single-unit recording from rat trigeminal ganglion, PGD 2 failed to sensitize meningeal nociceptors (34).…”
Section: Discussionmentioning
confidence: 95%
“…Its effect on peripheral afferents is less clear. In cultured DRG neurons, PGD 2 evoked an accumulation of cAMP (25) and increased the amplitude of TTX-resistant Na ϩ currents via the DP 1 receptor (7). In nodose neurons, PGD 2 inhibited postspike hyperpolarization, resulting in an increase in the firing frequency (5).…”
Section: Discussionmentioning
confidence: 99%
“…Given that NP-1 does not have a known signaling function, we next examined other signaling pathways that could be responsible for mediating VEGF-dependent inhibition of DRG growth cone collapse. Prostaglandins exert direct effects on sensory neurons via specific EP and IP receptors (37)(38)(39)(40) and also mediate biological functions of VEGF (12,16). The role of prostanoids in regulating neurotrophic or growth cone activity has not been examined previously, however (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the effect elicited by 1 M butaprost is not restricted to the EP2 receptor and may be mediated by activation of other prostanoid receptors. In addition, butaprost at micromolar concentrations binds to the mouse IP receptor (57), and IP receptor agonists increase icAMP content in sensory neurons (18,62). Since IP receptor expression was not affected by antisense treatment to EP3C and EP4, there are sufficient IP receptors available to potentially mediate the actions of butaprost.…”
Section: Discussionmentioning
confidence: 99%